Magnetically Recyclable Silica-Coated Magnetite-Molybdate Nanocatalyst and its Applications in N-Formylation Reactions Under Solvent-Free Conditions - Tandon, Runjhun; Patil, Shripad; Tandon, Nitin; Kumar, Pushpendra (Letters in Organic Chemistry, 2022)
A novel magnetite silica-coated nanoparticle-supported molybdate nanocatalyst has been prepared successfully by a simple co-precipitation method. Prepared nanocatalyst has been characterized by different techniques like Fourier Transmission Infrared Spectroscopy (FT-IR), X-ray diffraction (XRD), Field Emission Scanning Electron Microscope (FE-SEM), and Energy Dispersive X-ray Spectroscopy (EDX). Further, the catalytic activity of the nanocatalyst was explored for N-formylation reactions under solvent-free conditions. Interestingly, the catalyst could be reused for 10 cycles, and only 2 mol % of the catalyst was sufficient to catalyze the N-formylation reaction at 70°C under solvent-free conditions.
Keywords: green chemistry